2010
DOI: 10.1007/s10802-010-9461-7
|View full text |Cite
|
Sign up to set email alerts
|

Social Withdrawal Subtypes during Early Adolescence in India

Abstract: The overarching goal of this study was to examine the associations between three social withdrawal subtypes (shyness, unsociability, avoidance), peer isolation, peer difficulties (victimization, rejection, exclusion, low acceptance), and loneliness in India during early adolescence. Participants were 194 adolescents in Surat, India (M age = 13.35 years). Peer nominations of peer relations and socioemotional behaviors were gathered, along with self-reports of reasons for being alone and loneliness. Preliminary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
210
3
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(234 citation statements)
references
References 42 publications
19
210
3
2
Order By: Relevance
“…For instance, in a series of studies, Coplan et al (2004;Coplan and Weeks 2010) demonstrated that teacher-and parent-reported shyness and unsociability are distinct subtypes of withdrawal during early and middle childhood, and that although unsociability carries some risk, the psychosocial risks (e.g., anxiety, peer difficulties) associated with shyness are significantly greater. Similar findings have emerged during early adolescence (10-14 years), with compelling evidence that the distinctions between shyness, unsociability, and avoidance are meaningful, and that relative to unsociability, the psychological (e.g., loneliness; depressive symptomology) and peer difficulties (e.g., peer exclusion, peer victimization) associated with shyness and avoidance are greater (Bowker and Raja 2011;Coplan et al 2006). Specific processes accounting for these differential risks have not yet been tested.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…For instance, in a series of studies, Coplan et al (2004;Coplan and Weeks 2010) demonstrated that teacher-and parent-reported shyness and unsociability are distinct subtypes of withdrawal during early and middle childhood, and that although unsociability carries some risk, the psychosocial risks (e.g., anxiety, peer difficulties) associated with shyness are significantly greater. Similar findings have emerged during early adolescence (10-14 years), with compelling evidence that the distinctions between shyness, unsociability, and avoidance are meaningful, and that relative to unsociability, the psychological (e.g., loneliness; depressive symptomology) and peer difficulties (e.g., peer exclusion, peer victimization) associated with shyness and avoidance are greater (Bowker and Raja 2011;Coplan et al 2006). Specific processes accounting for these differential risks have not yet been tested.…”
Section: Introductionmentioning
confidence: 75%
“…However, not all withdrawn youth experience peer and other psychosocial difficulties; in the aforementioned studies, the associations between the subtypes and peer difficulties such as peer rejection, victimization, and exclusion, were only small-to-moderate in size (e.g., rs = .19-.23, Bowker and Raja 2011). Given that peer difficulties are one mechanism by which the withdrawal subtypes lead to psychological maladaptation (Bowker and Raja 2011;Boivin et al 1995), additional research addressing why some withdrawn youth are particularly at risk for peer difficulties could help improve the specificity of etiological theories of social withdrawal during childhood and adolescence, as well as intervention and prevention efforts, which to date have been relatively limited in their effectiveness (Greco and Morris 2001).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…This prediction was supported by a recent study conducted in Chinese rural areas, showing that unsociability was associated with adjustment problems including peer rejection, school incompetence, and depression [34]. It was mainly because unsociable behavior was regarded as being selfish and threatening the group well-being in more collectivistic societies [25,40]. The limited previous empirical research in urban areas also provided the evidence showing that unsociable children encounter maladjustment [25,41,42].…”
Section: Unsociabilitymentioning
confidence: 65%